2014
DOI: 10.1002/asi.23004
|View full text |Cite
|
Sign up to set email alerts
|

What influences online deliberation? A wikipedia study

Abstract: In this paper we describe a study aimed at evaluating and improving the quality of online deliberation. We consider the rationales used by participants in deletion discussions on Wikipedia in terms of the literature on democratic and online deliberation and collaborative information quality. Our findings suggest that most participants in these discussions were concerned with the notability and credibility of the topics presented for deletion, and that most presented rationales rooted in established site polici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…A differentiating feature of the voter in the previous example is the citation of relevant and targeted policy, Notability (geographic features). In prior work, this citation behavior was previously noted as highly relevant for further study [65]; in particular, they noted that locations, biographies, and corporate pages were deleted at substantially different rates compared to pages in general. Our research extends that finding: Notability policies are among the most informative votes in our forecast model, appear early in debates (particularly often in Keep votes), and are more successful in general than other policies and more than votes in general.…”
Section: Notability Policiesmentioning
confidence: 71%
See 2 more Smart Citations
“…A differentiating feature of the voter in the previous example is the citation of relevant and targeted policy, Notability (geographic features). In prior work, this citation behavior was previously noted as highly relevant for further study [65]; in particular, they noted that locations, biographies, and corporate pages were deleted at substantially different rates compared to pages in general. Our research extends that finding: Notability policies are among the most informative votes in our forecast model, appear early in debates (particularly often in Keep votes), and are more successful in general than other policies and more than votes in general.…”
Section: Notability Policiesmentioning
confidence: 71%
“…Along with measuring any particular user behavior, like arriving early or posting frequently, we will also single out specific policies that are often cited in exemplar cases of that behavior. This is a useful analytic lens; policies have consistently been a focus area of AfD research, from the close study of the Ignore All Rules policy in [33] to the study of notability subpolicies in [65]. The broad theme of our findings is that the relationship between policy citation, success, and forecast shift is nuanced.…”
Section: Analysis With the Forecast Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…From an argumentation study perspective, offering one's rationales has the power to persuade others and to bolster one's credibility (Aristotle, ) and promote one's and peers’ reflective thinking process (Xiao & Carroll, ). Research on online deliberations indicated the importance of understanding the shared rationales in these activities in collective decision‐making (Graham & Witschge, ; Xiao & Askin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al (2013) investigated the difference in arguments from novices and experienced users. Xiao and Askin (2014) examined the types of rationales in Wikipedia AfD discussions.…”
Section: Introductionmentioning
confidence: 99%